2000
DOI: 10.1103/physrevlett.85.5364
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Mechanical Properties ofC70Fullerene and Graphite under High Pressures Studied Using Designer Diamond Anvils

Abstract: We compare electrical and mechanical properties of C70 fullerene with high purity graphite to 48 GPa at room temperature using designer diamond anvils with embedded electrical microprobes. The electrical resistance of C70 shows a minimum at 20 GPa with transformation to an amorphous insulating phase complete above 35 GPa, while graphite remains conducting. Nanoindentation shows hardness values 220 times larger for the pressure quenched amorphous phase than for similarly treated graphite. Our studies establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
89
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 11 publications
4
89
0
Order By: Relevance
“…This result is consistent with experimental observations [10,11]. It should be noted that the 100 GPa strength of the graphite and the diamond is obtained under a nonuniform compressive condition where shear stress may play important role.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…This result is consistent with experimental observations [10,11]. It should be noted that the 100 GPa strength of the graphite and the diamond is obtained under a nonuniform compressive condition where shear stress may play important role.…”
supporting
confidence: 81%
“…In the last decade, many high-pressure experiments have revealed the fascinating phase transformation of fullerenes into superhard polymeric and disordered-amorphous carbon phases. The hardness sometimes can approach that of single-crystal diamond [3][4][5][6][7][8], even at room temperature [9,10]. On the other hand, in graphite subjected to high pressure up to 65 GPa at room temperature, no superhardness is found after the pressure is removed [10,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another little understood carbon allotrope is a transparent superhard carbon polymorph. It is observable under a high pressure range of 10-25 GPa, [15][16][17][18][19][20][21] but only quenchable at low temperatures (<100 K) and at ambient pressure. 15 This post-graphite phase has been extensively explored to identify candidate crystal structures, including sp 2 -sp 3 hybrid (3,0)/(4,0), 22 and sp 3 -hybridized M-carbon, bct-C 4 , F-carbon, X-carbon, Y-carbon, W-carbon, Z-carbon, and P-carbon.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] But in a long time, the accurate conductivity measurements were ever hard to be taken on diamond anvil cell (DAC) due to the difficulties from sample configuration and the rigorous geometrical limitations coming from small sample and electrodes. [5][6][7][8][9][10][11][12] For solving the problem, the techniques of thin film electrodes integration and electric field analysis (EFA) were combined together in conductivity measurement by four-probe method (FPM) in DAC and the accuracy has been achieved. [13][14][15][16] These studies indicated that only if the size and the thickness of sample chamber and the geometry configuration of electrodes were carefully designed, could the conductivity be obtained by FPM configuration and EFA methods.…”
mentioning
confidence: 99%